2022
DOI: 10.25258/ijddt.12.3.05
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Rose Bengal Dye from Aqueous Solution using Low Cost (SA-g-PAAc) Hydrogel: Equilibrium and Kinetic Study

Abstract: Hydrogels are considered one of the most important polymers, with very low economic costs for treating dyes from an aqueous solution. In this study, sodium alginate (SA), a kind of polysaccharide, and acrylic acid is an organic compound, N-Methylene-bis-acrylamide (MBA) as a cross-linked agent, were used to prepare the hydrogel by free radical method. Studies have shown that sodium lignite-based nano-hydrogel is environmentally friendly, more cost-effective and highly efficient in remove dye in aqueous solutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The volume of NaNO 2 salt has an effective part in this reaction so it has been studied and determined the best volume, which leads to a fast and higher absorbance.The data indicated that the better volume of Sodium nitrite salt 3 mL for dopamine and adrenaline as appear in Figure 4.The better time for the reaction complete and the formation of the diazonium salt was about 5 minutes, several periods of time were studied among 2-60 minutes 12,13,17,18 as appeared in Figure 5.…”
Section: Influence Of Volume Of Nano 2 Salt and Timementioning
confidence: 93%
See 1 more Smart Citation
“…The volume of NaNO 2 salt has an effective part in this reaction so it has been studied and determined the best volume, which leads to a fast and higher absorbance.The data indicated that the better volume of Sodium nitrite salt 3 mL for dopamine and adrenaline as appear in Figure 4.The better time for the reaction complete and the formation of the diazonium salt was about 5 minutes, several periods of time were studied among 2-60 minutes 12,13,17,18 as appeared in Figure 5.…”
Section: Influence Of Volume Of Nano 2 Salt and Timementioning
confidence: 93%
“…Spectrophotometric methods carry out for the estima-tion of adrenaline utilizing different reagents like ferric chloride and chloranil, in the found of potassium hexa-cyanoferrate (III), or n the presence (1,10-phenanthroline). 1,4,[10][11][12][13][14][15] The values of the [(SD), and (RSD%)] for these imitate measurements of the drugs.…”
Section: Introductionmentioning
confidence: 99%
“…The highest and lowest values of the elements that existed in the modified MWCNT/ZnO were 76.0 and 10.8 wt.%. 20,21…”
Section: Characterizationmentioning
confidence: 99%
“…They are prevalent in various fields, including medicine, agriculture, food production, biotechnology, and pharmacy. A significant use of hydrogels is their role in controlling the release of pharmaceuticals [1][2][3][4]. The polymers, monomers, and cross-linking substances used in hydrogel production can greatly influence their physical and chemical properties.…”
Section: Introductionmentioning
confidence: 99%